2010
DOI: 10.1186/1742-2094-7-49
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α sensitizes spinal cord TRPV1 receptors to the endogenous agonist N-oleoyldopamine

Abstract: Modulation of synaptic transmission in the spinal cord dorsal horn is thought to be involved in the development and maintenance of different pathological pain states. The proinflamatory cytokine, tumor necrosis factor α (TNFα), is an established pain modulator in both the peripheral and the central nervous system. Up-regulation of TNFα and its receptors (TNFR) in dorsal root ganglion (DRG) cells and in the spinal cord has been shown to play an important role in neuropathic and inflammatory pain conditions. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 44 publications
2
22
1
Order By: Relevance
“…It is also known that TNF-α can directly activate TNF-α receptors on peripheral nerve terminals, amplify hyperalgesic responses (Cunha et al, 1992;Junger and Sorkin, 2000), and release enzymes to enhance inflammation. It has been shown that TNF-α mediated increase in TRPV1 promotes painful inflammatory processes locally, impacting subsequent responses in the immune system (Spicarova and Palecek, 2010). Kochukov et al also demonstrated up-regulation of TRP channel in human synovial cells after preincubation with TNFα (Kochukov et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that TNF-α can directly activate TNF-α receptors on peripheral nerve terminals, amplify hyperalgesic responses (Cunha et al, 1992;Junger and Sorkin, 2000), and release enzymes to enhance inflammation. It has been shown that TNF-α mediated increase in TRPV1 promotes painful inflammatory processes locally, impacting subsequent responses in the immune system (Spicarova and Palecek, 2010). Kochukov et al also demonstrated up-regulation of TRP channel in human synovial cells after preincubation with TNFα (Kochukov et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We have observed that there is a significant increase in the levels of pro-inflammatory mediators IL-1β, IL-6 and TNF-α. These mediators can interact with TRPV1 expressing cells and alter TRPV1 expression and function [41,42]. Peripheral inflammation (intraplantar CFA-treatment) and peripheral nerve injury (CCI) have been shown to increase the levels of phosphorylated p38 and ERK in spinal cord tissue [43 -49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TRPV1 is receptive to pro-inflammatory agents such as prostaglandins, bradykinin, adenosine triphosphate (ATP), 5-hydroxytryptamine, protease activate receptors (PAR) 1, 2 and 4, nerve growth factor (NGF) and tumor necrosis factor alpha (TNF-alpha) [50] that cause allosteric modification of the channel protein, either directly or indirectly, such that the probability of channel opening by heat, protons and capsaicin is enhanced [9,40,43,[51][52][53][54] Fig. (1).…”
Section: Trpv1 As Polymodal Sensor Expressed On Peptidergic Sensory Nmentioning
confidence: 99%